PERLINDUNGAN HUKUM ATAS HAK PRIVASI DAN KERAHASIAAN IDENTITAS PENYAKIT BAGI PASIEN COVID-19 - Indah Maria Maddalena Simamora (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2022)
Covid-19 patients are just like any other disease patient. Covid-19 patients also have the same rights and obligations as other patients. As in the Law of the Republic of Indonesia Number 36 of 2009 concerning Health in Article 5 paragraphs 1 and 2 "Everyone has the same rights in obtaining access to resources in the health sector." "Everyone has the right to obtain safe, quality, and affordable health services." Basically, every patient has the right to privacy and confidentiality of the illness they suffer, including their medical data. This is regulated in Article 32 letter i of Law Number 44 of 2009 concerning Hospitals. Constitutionally, the State protects the privacy and data of citizens. Everyone has the right to personal protection, family, honor, dignity and property under his control, and has the right to a sense of security and protection from the threat of fear to do or not do something which is a human right. this indirectly makes the state has a legal obligation as the personal protector of every citizen. It should be understood that one of the hospital's obligations is to respect and protect the rights of patients. Violation of the hospital's obligations will be subject to administrative sanctions in the form of a warning, written warning, or fine and revocation of the hospital's permit. Thus, if the hospital does not protect the identity of its patient who is positive for COVID-19, the hospital may be subject to administrative sanctions. In the event that the perpetrator of spreading the patient's identity above is a doctor or dentist who intentionally does not fulfill the obligations in Article 46 paragraph (1) and Article 51 letter c of Law 29/2004, then they can be punished.